Perceptions of The Seriousness of Mispronunciations of English Speech Sounds - Moedjito Moedjito; ITO Harumi (TEFLIN, 2006)
The present study attempts to investigate Indonesian EFL teachersÃ¢â¬â¢ and native English speakersÃ¢â¬â¢ perceptions of mispronunciations of English sounds by Indonesian EFL learners. For this purpose, a paper-form questionnaire consisting of 32 target mispronunciations was distributed to Indonesian secondary school teachers of English and also to native English speakers. An analysis of the respondentsÃ¢â¬â¢ perceptions has discovered that 14 out of the 32 target mispronunciations are pedagogically significant in pronunciation instruction. A further analysis of the reasons for these major mispronunciations has reconfirmed the prevalence of interference of learnersÃ¢â¬â¢ native language in their English pronunciation as a major cause of mispronunciations. It has also revealed Indonesian EFL teachersÃ¢â¬â¢ tendency to overestimate the seriousness of their learnersÃ¢â¬â¢ pronunciations. Based on these findings, the study makes suggestions for better English pronunciation teaching in Indonesia or other EFL countries.